A new liver regeneration molecular mechanism involving hepatic stellate cells, Kupffer cells, and glucose‐regulated protein 78 as a new hepatotrophic factor. (31st May 2022) - Hagiwara, Kei; Harimoto, Norifumi; Yamanaka, Takahiro; Ishii, Norihiro; Yokobori, Takehiko; Tsukagoshi, Mariko; Watanabe, Akira; Araki, Kenichiro; Yoshizumi, Tomoharu; Shirabe, Ken
Abstract: Background/Purpose: To overcome liver failure, we focused on liver regeneration mechanisms by the activation of hepatic stellate cells (HSCs) and Kupffer cells (KCs). It is known that the HSC‐secreted Mac‐2‐binding protein glycan isomer (M2BPGi) activates KC in the fibrotic liver. However, its importance for liver regeneration of the HSCs/M2BPGi/KCs axis after hepatectomy is still unknown. The aim of this study was to clarify whether the HSC‐derived M2BPGi can activate KCs after hepatectomy, and elucidate the new molecular mechanism of liver regeneration. Methods: We examined the effect of M2BPGi on human hepatocytes and KCs, and explored secretory factors from M2BPGi‐activated KCs using proteomics. Furthermore, the effect on liver regeneration of glucose‐regulated protein 78 (GRP78) as one of the M2BPGi‐related secreted proteins was examined in vitro and in murine hepatectomy models. Results: Although M2BPGi had no hepatocyte‐promoting effect, M2BPGi promoted the production of GRP78 in KCs. The KC‐driven GRP78 promoted hepatocyte proliferation. GRP78 administration facilitated liver regeneration after 70% hepatectomy and increased the survival rate after 90% hepatectomy in mice. Conclusions: The M2BPGi‐activated KCs secrete GRP78, which facilitates liver regeneration and improves the survival in a lethal mice model. Our data suggest that the new hepatotrophic factor GRP78 may be a promising therapeutic tool for lethal liver failure. Abstract : Hagiwara and colleagues report on the new hepatotrophic factor glucose‐regulated protein 78 (GRP78) produced by Kupffer cells (KCs). Mac‐2‐binding protein glycan isomer (M2BPGi) produced by hepatic stellate cells activates KCs. The M2BPGi‐activated KCs secrete GRP78, and GRP78 facilitates liver regeneration and improves the survival in a lethal mouse model.